Glycerol and Methanol Electro-oxidation at Pt/C-ITO under Alkaline Condition - Ottoni, Cristiane Angelica [UNESP]; Domingues Ramos, Carlos Eduardo; Silva, Sirlane Gomes da; Spinace, Estevan Vitorio [UNESP]; Brambilla de Souza, Rodrigo Fernando; Oliveira Neto, Almir (Wiley-Blackwell, 2016)
A physical mixture composed by carbon Vulcan XC 72 and indium tin oxide (ITO) with different ratios (85 : 15; 50 : 50; 85 : 15) was used as support for platinum nanoparticles synthesis by borohydride reduction method. The characterization of this electrocatalyst was performed by transmission electron microscopy (TEM), X-ray diffraction (XRD), electrochemical techniques cyclic voltammetry (CV), chronoamperometry and performance test on direct alkaline glycerol/methanol fuel cell (DGFC/DMFC). According to TEM micrographs, Pt/C-ITO nanoparticles analysis revealed the presence of large agglomerations of particles. Moreover, it was possible to serve Pt deposition on ITO and also in the carbon surface. The electrochemical studies showed that Pt/C-ITO (85 : 15) had superior performance for glycerol electro-oxidation, whereas Pt/C-ITO (15 : 85) was the most promising in the methanol oxidation. A comparative study using direct alkaline fuel cells revealed Pt-C-ITO (15 : 85) electrocatalyst to be the best material for glycerol and methanol oxidation, specifically when being at open circuit potential about 0.95 V, maximum power density of 16 mW cm(-2) for glycerol and circuit potential 0.95 V, and maximum power density of approximately 20 mW cm(-2) for methanol.
Keywords: Pt/C-ITO electrocatalysts; Direct alkaline fuel cell; Glycerol oxidation reaction